What we don't talk about when we talk about fat [book club bag] - Gordon, Aubrey (Beacon Press, 2020)
"From the creator of Your Fat Friend, an explosive indictment on the systemic and cultural issues facing plus-sized people that will move us toward creating an agenda for fat justice"--